Rhetoric of the construction of the subject and the construction of the object in the similarity of pronouncement in the Quran - Aouarib, Salim (Milev Journal of Research and Studies, 2021)
One of the secrets of the rhetoric of similar verbal similarity in the Quran is that linguistic methods are consistent with different contexts. We often find verses with similar words in which the verb comes in one of them based on the subject, and in the other based on the object, and this is to achieve different rhetorical purposes and make semantic differences. Therefore, this research aims to discuss the issue of difference the significance of the composition between mentioning the subject and his deletion, in an attempt to answer the problem of constructive rhetoric for the subject and constructing the object, by analyzing some verses with similar words in the noble quran, with differ in terms of the verb construction formula for the known or unknown, so that the researche researches the achievement of a set of results,including: that deleting the subject indicates interest in the action, highlighting the event, and indicating the extent to which the latter is related to its effect